Chinese College Students' Stress and Anxiety Levels Under COVID-19 - Zhan, Huali; Zheng, Chunmei; Zhang, Xianqin; Yang, Meng; Zhang, Lin; Jia, Xu (Frontiers in Psychiatry, 2021)
The outbreak of COVID-19 at the end of 2019 has had a significant impact on people. While attention is paid to the immense physical harm it has caused, the psychological impact should not be underestimated. The main purpose of this study was to explore the stress, anxiety, and depression levels of different groups of college students before and after resuming school during the COVID-19 pandemic. We conducted an online questionnaire survey of college students by using the Perceived Stress Scale (PSS-10), the Patient Health Questionnaire-9 items (PHQ-9), and the Self-rating Anxiety Scale (SAS). A total of 1,586 questionnaires were collected and analyzed in R language. The results showed that students with moderate to severe stress (PSS-10≥14) accounted for 67.50%; the detection rate of depression (PHQ-9≥5) reached 43.77%; and 20.60% of students had anxiety (SAS standard score≥50). There were significant differences in PSS-10/SAS among different genders, majors, whether returning to school or not, and those with different psychological experiences (negative or positive, P<0.05). It is notable that the median of female, medical student, non-resumption of schooling, and negative experience was higher than that of positive experience (P<0.05). The results of principal component analysis showed that there were significant differences in PHQ-9, PSS-10, and SAS between the resumption of schooling group and the non-resumption group. Therefore, it is inferred that the stress and anxiety level of college students before and after resuming school during the COVID-19 pandemic is generally high, especially for those who have not yet resumed school. Long-term negative emotions can easily lead to serious mental diseases such as cognitive impairment. Education departments should attach great importance to the mental health of college students, and it is necessary to provide precise psychological interventions for groups experiencing greater pressure levels and marked anxiety and depression.